The Influence of Organizational Culture, Whistleblowing System, and the Role of Internal Control on Fraud Prevention in Hospitals - Hartanti, Firli Adelia; Paranoan, Selmita; Ansar, Muhammad; Yuniar, Latifah Sukmawati (Penelitian dan Pengembangan Ilmu, 2024)
This study aims to analyze the effect of organizational culture, whistleblowing system, and the role of internal control on fraud prevention at Undata Hospital, Palu City. Primary data collection was carried out using a quantitative approach, namely by distributing questionnaires to 40 employees in the finance staff, education, training and research staff (Diklit), equipment & general staff, and medical service staff. The sampling technique used was random sampling. Data analysis using WarpPLS 7.0. The results showed that organizational culture has no effect on fraud prevention, while the whistleblowing system and internal control have a positive and significant effect on fraud prevention. This study uses a combination of internal control, organizational culture, and whistleblowing system in a hospital environment as a topic of fraud prevention that has not received much attention in previous studies. The conclusion of this study is that, to improve fraud prevention efforts in hospitals, it is very important to strengthen internal control and whistleblower systems.